PENGARUH PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMANDIRIAN BELAJAR SISWA DI SDN 16 TALANG KELAPA - Ayu Annur Fani; Karoma; Arvin Efriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the influence of Artificial Intelligence (AI) utilization on students’ learning independence at SDN 16 Talang Kelapa. The study employed a quantitative approach using a survey method with a correlational research design. The research population consisted of 120 students, with a sample of 92 students selected through simple random sampling. Data were collected through questionnaires as the primary instrument, supported by observation and interviews. The results showed that the utilization of Artificial Intelligence had a positive and significant effect on students’ learning independence. This was evidenced by the hypothesis test result showing that the t-value of 5.842 was greater than the t-table value of 1.990, with a significance value of 0.000 < 0.05. The coefficient of determination test showed an R² value of 0.438, indicating that Artificial Intelligence utilization contributed 43.8% to students’ learning independence, while the remaining percentage was influenced by other factors outside this study. The findings indicate that the use of Artificial Intelligence can improve learning initiative, exploration of learning resources, learning responsibility, and students’ ability to manage their learning process independently. Therefore, the appropriate utilization of Artificial Intelligence can serve as an effective strategy to support the improvement of elementary school students’ learning independence.